Classification for treatment urgency for the microphthalmia/anophthalmia spectrum using clinical and biometrical characteristics. Issue 5 (25th February 2020) - Groot, Annabel L.W.; Kuijten, Maayke M.P.; Remmers, Jelmer; Gilani, Asra; Mourits, Daphne L.; Kraal‐Biezen, Elke; de Graaf, Pim; Zwijnenburg, Petra J.; Moll, Annette C.; Tan, Stevie; Saeed, Peerooz; Hartong, Dyonne T.
Abstract: Purpose: Current clinical classifications do not distinguish between the severity of the MICrophthalmia/Anophthalmia (MICA) spectrum with regard to treatment urgency. We aim to provide parameters for distinguishing mild, moderate and severe MICA using clinical and biometrical characteristics. Methods: We performed a single‐centre, cross‐sectional analysis of prospective cohort of 58 MICA children from September 2013 to February 2018 seen at the Amsterdam University Medical Center, The Netherlands. All patients with a visible underdeveloped globe were included. We performed full ophthalmic evaluation including horizontal palpebral fissure length, axial length by ultrasound and/or MRI measurements, paediatric and genetic evaluation. Cases were subdivided based on clinical characteristics. Biometrical data were used to calculate the relative axial length (rAL) and the relative horizontal palpebral fissure length (rHPF) compared with the healthy contralateral eye for unilateral cases. Results: In previously untreated patients, a strong correlation exists between rAL and rHPF, distinguishing between severe, moderate and mild subjects using rAL of 0–45%, 45–75% and 75%–100%, respectively. Clinical subgroups were randomly dispersed throughout the scatterplot. Conclusion: Current classifications lack clinical implications for MICA patients. We suggest measuring eyelid length and axial length to classify the severity and determine treatment strategy. The 'severe' group has obvious asymmetry and abnormal socket configuration for which therapy should quickly be initiated; the 'moderately' affected group has normal socket anatomy with a microphthalmic eye with disturbing asymmetry for which treatment should be initiated within months of development; the 'mild' group has a slightly smaller axial length or less obvious eyelid asymmetry for which reconstructive correction is possible, but expansive conformer treatment is unnecessary.